2020
DOI: 10.1177/1455072520941977
|View full text |Cite
|
Sign up to set email alerts
|

Successes and failures in treatment of substance abuse: Treatment system perspectives and lessons from the European continent

Abstract: Objective: The article offers an inventory of controversial basic issues related to treatment responses and their sociocultural political context, highlighting policy failures and successes, with a focus on Europe. As a reference point for this assessment, serves a conceptual framework of an “ideal type of treatment system”, which is built upon the following normative assumptions: the objective of harm minimisation or preventing substance-use-related consequences, evidence-based decision making, securing equit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…cost-benefit) to consider the long-term benefits of SUT on the prevention CJS contact. Another advantage of the current research is that it provides insights outside the Global North context [34,35] into the outcomes associated with SUT at a system level (including data from multiple centres and programmes).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…cost-benefit) to consider the long-term benefits of SUT on the prevention CJS contact. Another advantage of the current research is that it provides insights outside the Global North context [34,35] into the outcomes associated with SUT at a system level (including data from multiple centres and programmes).…”
Section: Discussionmentioning
confidence: 99%
“…While all cited studies have significantly contributed to our knowledge, most of them come from western contexts (e.g. the United States and western Europe), and other contexts are relatively underexplored [34,35]. The Chilean SUT policy is an interesting case study, as it has one of Latin America's oldest and most developed SUT systems.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, difficulties in managing users due to their own specific individual needs can limit the effectiveness of these strategies and so, without regular reviewing, possible modifications that would improve an individual's rehabilitation success is ignored (Leukefeld and Tims, 1993). The allocation of resources and stigma can also have a negative impact (Klingemann, 2020). Sondhi and Day (2012) found that while male prisoners did havehad high expectations of the IDTS, they felt their treatment they received did not match their prior assumptions.…”
Section: Rehabilitation Techniquesmentioning
confidence: 99%
“…Unsuccessful treatment can have very negative consequences for the individual and society. Some of the outcomes of unsuccessful treatment include relapse and recidivism after treatment [12][13][14], negative psychological and social performance, poor educational or occupational status [15], participation in criminal behavior [16,17], and social costs, for example, pressure on family and society [7].…”
Section: Introductionmentioning
confidence: 99%